INVESTIGATION OF TOTAL PHENOLIC, TOTAL FLAVONOID, ANTIOXIDANT AND ALLYL ISOTHIOCYANATE CONTENT IN THE DIFFERENT ORGANS OF WASABI JAPONICA GROWN IN AN ORGANIC SYSTEM - Shin, Seong Woo; Ghimeray, Amal Kumar; Park, Cheol Ho (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: This study was carried out to investigate the total polyphenol (TP), total flavonoid (TF), antioxidative effect and allyl isothyocyanate (ITC) content in different organs of wasabi plant grown in an organic system. Materials and Methods: Invitro study of methanol and boiled water extracts of wasabi were conducted by analyzing the 1-1- diphenyl-2-picryl hydrozyl (DPPH) radial scavenging activity, metal chelating activity and total antioxidant capacity in a comparative manner. Result: The result revealed that methanol extract showed higher TP in flower (3644 mg TAE/100 g dw), leaf (3201 mg TAE/100 g dw) and fruit (3025 mg TAE/100 g dw) as compared to the boiled water extract. Similarly, TF content was also higher in methanol extracts of flower (1152 mg QE/100 g dw) and leaf (325 mg QE/100 g dw), however, the other parts showed ignorable value.Results: Results of antioxidant activity were found at different magnitude of potency. The methanol extract of different parts of wasabi exhibited higher activity in total antioxidant capacity and DPPH radical scavenging assay as compared to water extract. In metal chelating assay, the boiled water extracts of leaf showed higher (76.9%) activity, followed by fruit (68.8%) and flower (62.8%). Ally ITC detected by gas chromatography was present in all of the tissues of wasabi plant but the content was found to be varied in different tissues. Conclusions: Overall, this study will allow consumers and processors to understand the possibility for medical application of wasabi plant by knowing the level of total polyphenol distribution, Ally ITC content and antioxidant property distributed in different parts and tissues.